2022
DOI: 10.3390/catal12070695
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Tri-Coordination Zinc Complex Functionalized Silicotungstate with ROS Catalytic Ability and Anti-Tumor Cells Activity

Abstract: Reactive oxygen species (ROS) can be used as an effective method to treat tumors. Artificial oxidase has received increasing attention as a catalyst for ROS generation in fields ranging from bioinorganic chemistry to pharmaceutical chemistry. In this study, an artificial oxidase based on a binuclear zinc complex and Keggin-type silicotungstate [Zn2(4,4′-bpy)(Phen)2][SiW12O40] (ZSW) (4,4′-bpy = 4,4′-bipyridine; Phen = 1,10-phenanthroline) was synthesized and structurally featured in terms of its X-ray photoelec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…The Cu centers can easily be reduced or oxidized in dynamic equilibrium of structural transformation, and thus catalyze the production of ROS, which can be attributed to Cu ions catalyzing Haber–Weiss system reactions [ 1 , 52 , 53 ]. Recently, it was found that trans-metal ion-substituted POMs possess a strong catalytic ability to produce ROS [ 54 ]. The adsorption of H + to the POM skeleton may enhance the catalytic capacity of those complexes, since H + is an important product in Haber–Weiss system reactions [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Cu centers can easily be reduced or oxidized in dynamic equilibrium of structural transformation, and thus catalyze the production of ROS, which can be attributed to Cu ions catalyzing Haber–Weiss system reactions [ 1 , 52 , 53 ]. Recently, it was found that trans-metal ion-substituted POMs possess a strong catalytic ability to produce ROS [ 54 ]. The adsorption of H + to the POM skeleton may enhance the catalytic capacity of those complexes, since H + is an important product in Haber–Weiss system reactions [ 53 ].…”
Section: Discussionmentioning
confidence: 99%